Short-term psychotherapeutic treatment in adolescents engaging in non-suicidal self-injury: a randomized controlled trial - Fischer-Waldschmidt, Gloria; Brunner, Romuald; Parzer, Peter; Resch, Franz; Kaess, Michael (Trials, 2013)
BACKGROUND: Worldwide, prevalence rates of adolescent non-suicidal self-injury (NSSI) range between 13 and 45%. In Germany, lifetime prevalence of NSSI is around 25% in non-clinical samples, and the one-year prevalence for repetitive NSSI is 4%. NSSI is present in the context of several axis I and II disorders (for example, affective disorders or borderline personality disorder); however, preliminary evidence suggests that it would be justified to consider NSSI as its own diagnostic category. Despite the large impact of this behavior, there is still a lack of evidence-based, specific, and effective manualized treatment approaches for adolescents with NSSI. - METHODS/DESIGN: The study is designed as a randomized controlled trial (RCT) to test the effectiveness of a new cognitive-behavioral treatment manual for self-harming adolescents - the 'Cutting-Down-Programme' (CDP). A total of 80 adolescents aged between 12 and 17 years from a region in Southern Germany who have engaged in repetitive NSSI (≥5 incidents) in the last 6 months will be randomized into a treatment group (CDP) or a control group that will receive treatment as usual (TAU). The adolescents will be assessed by means of structured interviews and questionnaires at three time points (before treatment, directly after treatment and six months after treatment). Primary outcome criterion is a significant reduction (or remission) in the frequency of NSSI. Secondary outcome criteria are depressivity as well as general well-being and self-worth. Additionally, comorbid psychiatric disorders and childhood adversity will be evaluated as predictors of therapeutic outcome. - DISCUSSION: Recently, a pilot study in the United Kingdom showed significant reductions in self-harming behavior, depressive symptoms and trait anxiety. This is the first RCT to test the effectiveness of a short-term psychotherapeutic intervention in outpatients engaging in NSSI. - TRIAL REGISTRATION: The study is registered in the German Clinical Trials Register DRKS00003605.
Gesehen am 15.04.2021